2020
DOI: 10.1016/j.virol.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian orthoreovirus core protein μ2 reorganizes host microtubule-organizing center components

Abstract: Filamentous mammalian orthoreovirus (MRV) viral factories (VFs) are membrane-less cytosolic inclusions in which virus transcription, replication of dsRNA genome segments, and packaging of virus progeny into newly synthesized virus cores take place. In infected cells, the MRV μ2 protein forms punctae in the enlarged region of the filamentous VFs that are co-localized with γ-tubulin and resistant to nocodazole treatment, and permitted microtubule (MT)-extension, features common to MT-organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The core-only factories transitioned towards the nucleus when cycloheximide was employed to stop further virus amplification. Previous studies found that the µ2 protein associates with microtubules [48][49][50] and the current dogma is that these interactions mediate movement of viral factories. However past studies focused on late timepoints during infection when perinuclear factories predominant, and it would be interesting to revisit microtubule-µ2 associations with respect to whether they also support the movement of core-only factories.…”
Section: Discussionmentioning
confidence: 99%
“…The core-only factories transitioned towards the nucleus when cycloheximide was employed to stop further virus amplification. Previous studies found that the µ2 protein associates with microtubules [48][49][50] and the current dogma is that these interactions mediate movement of viral factories. However past studies focused on late timepoints during infection when perinuclear factories predominant, and it would be interesting to revisit microtubule-µ2 associations with respect to whether they also support the movement of core-only factories.…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence signal values in the VLSs were determined similarly, as described previously by Eichwald et al ( 95 ). The intensity profile of a linear region of interest was obtained using the ImageJ plot profile tool.…”
Section: Methodsmentioning
confidence: 99%
“…The core-only factories transitioned towards the nucleus when cycloheximide was employed to stop further virus amplification. Previous studies found that the μ2 protein associates with microtubules [50][51][52] and the current dogma is that these interactions mediate movement of viral factories. However past studies focused on late timepoints during infection when perinuclear factories predominant, and it would be interesting to revisit microtubule-μ2 associations with respect to whether they also support the movement of core-only factories.…”
Section: Plos Pathogensmentioning
confidence: 99%